Preparation method of pole piece, pole piece, battery and electric device
By heating and insulation during the preparation of the electrode sheet, the problem of poor battery circulation performance is solved, the cohesion and adhesion of the electrode sheet are improved, and the circulation performance and life of the battery are improved.
Patent Information
- Application Number
- CN202311157136.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
The battery exhibits performance deterioration and poor circulation performance during the cycle, resulting in a shorter battery life.
By performing heating and insulation treatment during the electrode sheet preparation process, the heating temperature and insulation temperature are controlled above the melting point or softening point of the binder, but are lower than the decomposition temperature, to promote the uniform distribution of the binder and release the stress in the electrode sheet.
It improves the cohesion and bonding force of the electrode sheet, improves the circulation performance and life of the battery, reduces the internal resistance of the battery and maintains the stability of the active substance.
Smart Images

Figure CN119601597A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a method for preparing a pole piece, a pole piece, a battery, and an electrical device. Background Art
[0002] As batteries are used in more and more scenarios, the market has put forward higher and higher requirements on various battery performances, and battery life is one of the key performances that affect the user experience of various electrical devices. Therefore, extending battery life is the key to promoting further development of batteries.
[0003] As an important component of the battery, the electrode has a key impact on the battery life. Therefore, the battery life can be improved by improving the electrode. However, during the battery cycle, the electrode often deteriorates in performance, resulting in poor cycle performance, which in turn shortens the battery life. Summary of the invention
[0004] In view of the above problems, the present application provides a method for preparing a pole piece, a pole piece, a battery, and an electrical device, which can solve the problem of poor battery cycle performance.
[0005] In a first aspect, the present application provides a method for preparing a pole piece, comprising:
[0006] An active layer comprising an active material and a binder is prepared on at least one side of the current collector;
[0007] Performing a heating treatment on the active layer to raise the surface temperature of the active layer to a heating temperature;
[0008] Performing heat preservation treatment on the active layer so that the surface of the active layer is at a heat preservation temperature;
[0009] The heating temperature and the insulation temperature are independently greater than or equal to the melting point or softening point of the binder, and less than the decomposition temperature of the binder.
[0010] The method of the embodiment of the present application is used to prepare the pole piece, so that the battery using the pole piece has good cycle performance, which is mainly due to:
[0011] (1) In the preparation method of the embodiment of the present application, the active layer is heated to raise the surface temperature of the active layer to or above the melting point or softening point of the binder, so that the binder is molten or softened. At the same time, the heat preservation treatment at the same temperature range can promote the re-movement of the binder molecular chains in the molten or softened state, thereby facilitating the uniform distribution of the binder in the active layer, facilitating the release of the internal stress of the pole piece, and increasing the cohesion and adhesion of the pole piece, which can ultimately improve the cycle performance of the battery.
[0012] (2) The redistribution of the binder includes the infiltration of the binder on the surface of the active layer into the interior of the active layer, which is conducive to reducing the binder on the surface of the active layer, thereby helping to increase the porosity of the surface of the active layer, accelerate the absorption rate of the electrode for the electrolyte, and make the electrode fully contact with the electrolyte, so as to effectively participate in the electrochemical reaction, reduce the internal resistance of the battery during the charge and discharge cycle, and thus improve the cycle performance of the battery.
[0013] (3) The temperature during the heating and heat preservation process is lower than the decomposition temperature of the binder. The binder will not decompose (ablate) during the heating and heat preservation process, which is beneficial to maintaining the total amount of binder in the active layer and improving the cohesion and adhesion of the electrode. At the same time, the active material will not be affected by the decomposition products of the binder during the heating and heat preservation process, which is further beneficial to improving the cycle performance of the battery.
[0014] (4) During the heating and insulation process, the moisture and residual impurities adsorbed in the active layer volatilize, which helps to reduce the reaction between the moisture in the electrode and the lithium salt in the electrolyte, thereby improving the interface stability of the electrode and improving the battery cycle performance.
[0015] In some embodiments, the heating temperature and the insulation temperature are independently less than or equal to the average value of the melting point or softening point of the binder and the decomposition temperature of the binder. In this way, the binder will not decompose (ablate) during the heating and insulation processes, which is beneficial to maintaining the total amount of binder in the active layer, improving the cohesion and adhesion of the pole piece, and preventing the decomposition residues of the binder from affecting the active material. Moreover, at this temperature, the binder can maintain a high viscosity and the flow amplitude will not be too large, which is beneficial to maintaining the stability of the pole piece structure.
[0016] In some embodiments, the heat preservation treatment time is greater than or equal to 0.1s, and optionally 0.1-2.5s. After a certain period of heat preservation, the adhesive in the molten or softened state on the surface has enough time to penetrate into the active layer, thereby balancing the distribution of the adhesive in the active layer.
[0017] In some embodiments, the insulation temperature is less than or equal to the heating temperature. The insulation temperature is equal to or lower than the heating temperature, which can not only maintain the melting or softening state of the binder and make the binder in a flowable state with high viscosity, but also the flow range of the binder will not be too large, which is conducive to maintaining the stability of the pole piece structure without powder falling.
[0018] In some embodiments, the melting point or softening point of the binder is 140-180°C, and the decomposition temperature of the binder is 300-350°C; the heating temperature and the insulation temperature are independently 170-230°C, and optionally 190-230°C. For different binders, the heating temperature and the insulation temperature can be set within a suitable range. Within the above heating temperature and insulation temperature range, the binder can be melted or softened without decomposition, and the active substance is not interfered by the binder residue, which is conducive to maintaining the structure and performance stability of the active substance.
[0019] In some embodiments, the active material includes lithium nickel cobalt manganese oxide; optionally, in the lithium nickel cobalt manganese oxide, the molar ratio of Ni, Co, and Mn is (1-8): (1-2): (1-3). The method of the embodiment of the present application can be used to prepare different lithium nickel cobalt manganese oxide positive electrode sheets, and the stability of the lithium nickel cobalt manganese oxide can be maintained during the preparation process, and the resulting battery has good cycle performance.
[0020] In some embodiments, the number average molecular weight of the binder is (35-150)×10 4 , optionally (45~150)×10 4 Generally, the melting point or softening point of the binder is usually related to its molecular weight. Within the number average molecular weight range, the binder has a lower melting point or softening point, which is helpful for implementing the heating and heat preservation steps of the embodiment of the present application at low temperature.
[0021] In some embodiments, the heating treatment and the heat preservation treatment each independently include laser irradiation treatment. Using laser as a heating source has the characteristics of high energy density in a short time and high heating efficiency, and can quickly heat the active layer to a desired temperature. At the same time, laser irradiation also has the characteristics of controllable power, controllable wavelength, and high stability, and can effectively control the temperature of the active layer within a desired range.
[0022] In some embodiments, the laser includes one or more of an infrared wavelength laser and a near-infrared wavelength laser. Optionally, the wavelength of the laser is 1000nm to 15μm. The pole piece has a strong absorption of infrared light and near-infrared light. When irradiated with a laser in this wavelength range, it has a high photothermal conversion efficiency and can heat the active layer to a desired temperature in a short time.
[0023] In some embodiments, the laser power in the heating step is 2000-4500 W, and optionally 2000-4000 W. Heating under high-power laser is conducive to rapidly raising the temperature of the active layer.
[0024] In some embodiments, the laser power in the heat preservation step is 80-200 W, and optionally 100-150 W. The heat preservation treatment under low-power laser can maintain the surface temperature of the active layer within the required temperature range without overheating.
[0025] In some embodiments, the method for preparing the pole piece further includes the step of compacting the pole piece after the heat preservation treatment. In the heating treatment step and the heat preservation treatment step, the binder in the active layer is redistributed, and the moisture and impurities absorbed in the active layer volatilize, which may cause the thickness of the pole piece to change. Therefore, compaction treatment after the heat preservation treatment is conducive to controlling the thickness of the pole piece, for example, the thickness of the pole piece can be made consistent before and after the heating and heat preservation treatment.
[0026] In a second aspect, the present application provides a pole piece, which is obtained according to the preparation method of the first aspect.
[0027] In the pole piece of the embodiment of the present application, the binder is evenly distributed, so that the pole piece has high bonding strength, high porosity, and low water content. It can still maintain good structural stability after a long period of charge and discharge cycles, which is beneficial to improving the cycle performance of the battery using the pole piece.
[0028] In a third aspect, the present application provides a battery, wherein the battery comprises the electrode described in the second aspect.
[0029] The above-mentioned pole piece has high bonding force, high porosity, low water content, and good structural stability. The battery containing the pole piece will also show good cycle performance and long battery life.
[0030] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the battery according to the third aspect.
[0031] The battery disclosed in the embodiment of the present application can be used in an electrical device using the battery as a power source, or in various energy storage systems using the battery as an energy storage element, to provide electrical energy. The above battery exhibits the advantages of good cycle performance and long life. Therefore, after the battery is applied to various electrical devices, it is beneficial to improve the user experience of various electrical devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0033] Figure 1A schematic diagram of a battery cell according to an embodiment of the present application;
[0034] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0035] Figure 3 A schematic diagram of a battery module according to an embodiment of the present application;
[0036] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application;
[0037] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0038] Figure 6 A schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application;
[0039] Figure 7 The cycle performance test results of the lithium ion batteries in Example 1 and Comparative Example 1 of the present application;
[0040] Figure 8 This is an XRD diagram of the nickel-cobalt-manganese-oxide lithium positive electrode sheet of Example 1 of the present application before and after heating treatment and heat preservation treatment;
[0041] Fig. 9 This is a SEM image of the nickel-cobalt-manganese-oxide lithium positive electrode sheet of Example 1 of the present application before and after the heating treatment and the heat preservation treatment;
[0042] Figure 8 and Fig. 9 Here, "before treatment" refers to before the heating treatment and the heat preservation treatment, and "after treatment" refers to after the heating treatment and the heat preservation treatment.
[0043] Reference numerals:
[0044] 01-shell, 02-cover, 03-electrode assembly, 04-battery cell, 05-battery module, 06-upper box, 07-lower box. DETAILED DESCRIPTION
[0045] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0047] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0048] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0049] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0050] In the description of the embodiments of the present application, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.
[0051] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0052] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0053] As an important component of batteries, electrodes have a key impact on battery life. However, during the battery cycle, the performance of electrodes often deteriorates, resulting in poor battery cycle performance.
[0054] Important components of the electrode include active materials, binders, etc., which have an important influence on the performance of the electrode. For example, lithium nickel cobalt manganese oxide, as a relatively excellent lithium-ion battery positive electrode active material, has been widely used in passenger cars, commercial vehicles and other power fields in recent years. Compared with lithium iron phosphate materials, lithium-ion batteries using lithium nickel cobalt manganese oxide as positive electrodes have greater energy density and better fast charging and low temperature performance. However, in practice, it is found that due to the influence of the synthesis process, for example, an excessive amount of lithium source is usually used in the process of synthesizing lithium nickel cobalt manganese oxide, which makes lithium nickel cobalt manganese oxide contain a lot of residual alkali, such as lithium oxide, lithium carbonate, etc. The presence of residual alkali makes lithium nickel cobalt manganese oxide easy to absorb moisture in the air. After being assembled into a secondary battery, these moisture reacts with the lithium salt in the electrolyte, causing the battery to produce gas and deteriorate the battery cycle performance.
[0055] At the same time, after the active material and binder are made into the active layer of the electrode, there are often problems such as poor binder distribution, uneven porosity distribution or too low porosity, which also affect the battery cycle performance.
[0056] In order to improve the cycle performance of the battery, the relevant technology has studied a variety of technical means. For example, by forming a coating layer on the surface of the active material, the interfacial interaction of the active material during the battery cycle is improved, thereby improving the battery cycle performance. However, the presence of the coating layer may be detrimental to the electronic or ion conductivity of the electrode, thereby causing the internal resistance of the battery to be high and reducing the battery cycle performance. For another example, by preparing the electrode by irradiation, the aging problem of the binder in the electrode is reduced, the stability of the electrode is improved, and the effect of improving the battery cycle performance is achieved. However, irradiation will cause the crystal form of the active material to be distorted, and the organic matter in the electrode will react to form residual free radicals during the irradiation process, thereby deteriorating the electrode capacity and making it difficult to effectively improve the battery cycle performance.
[0057] To solve the above problems, the embodiments of the present application improve the structure of the pole piece by heating and keeping the pole piece warm during the pole piece preparation process, and controlling the heating temperature and the keeping temperature within a certain range, thereby balancing the distribution of the binder in the pole piece, improving the porosity of the pole piece, reducing the moisture content of the pole piece, etc., and maintaining the stability of the active material, thereby improving the battery cycle performance.
[0058] The electrode sheets processed by the above method can be used to make batteries, and then used in various electrical devices, including but not limited to mobile phones, tablets, laptops, electric toys, electric tools, electric vehicles, electric cars, ships, spacecraft, etc.
[0059] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0060]
Pole piece preparation method
[0061] A first aspect of an embodiment of the present application provides a method for preparing a pole piece, comprising:
[0062] An active layer comprising an active material and a binder is prepared on at least one side of the current collector;
[0063] The active layer is heated to raise the surface temperature of the active layer to a heating temperature;
[0064] Performing heat preservation treatment on the active layer so that the surface of the active layer is at a heat preservation temperature;
[0065] The heating temperature and the insulation temperature are independently greater than or equal to the melting point or softening point of the binder, and less than the decomposition temperature of the binder.
[0066] In the preparation method of the pole piece of the embodiment of the present application, the surface layer of the active layer refers to the outermost layer of the active layer in contact with the outside world. Usually, the pole piece includes a current collector and an active layer disposed on at least one side of the current collector, so the surface layer of the active layer is usually also the surface layer of the pole piece. Generally, the area within 40% of the thickness of the pole piece from the outside to the inside along the thickness direction of the pole piece can be regarded as the surface layer of the pole piece.
[0067] The softening point is the temperature at which the three-dimensional long-range ordered state of the macromolecular chain structure of a non-crystalline polymer changes into a disordered viscous flow state. The melting point is the temperature at which the three-dimensional long-range ordered state of the macromolecular chain structure of a crystalline polymer changes into a disordered viscous flow state, and is the lower limit of the molding processing temperature of crystalline polymers. Generally, the melting point range is relatively narrow, while the softening point range is relatively wide. The decomposition temperature refers to the temperature at which the degradation of the molecular chain of a polymer in a viscous flow state will be aggravated when the temperature is further increased, and even the polymer molecular chain will be significantly degraded.
[0068] The method of the embodiment of the present application is used to prepare the pole piece, so that the battery using the pole piece has good cycle performance, which is mainly due to:
[0069] (1) In the preparation method of the embodiment of the present application, the active layer is heated to raise the surface temperature of the active layer to or above the melting point or softening point of the binder, so that the binder is molten or softened. At the same time, the heat preservation treatment at the same temperature range can promote the re-movement of the binder molecular chains in the molten or softened state, thereby facilitating the uniform distribution of the binder in the active layer, facilitating the release of the internal stress of the pole piece, and increasing the cohesion and adhesion of the pole piece, which can ultimately improve the cycle performance of the battery.
[0070] (2) The redistribution of the binder includes the infiltration of the binder on the surface of the active layer into the interior of the active layer, which is conducive to reducing the binder on the surface of the active layer, thereby helping to increase the porosity of the surface of the active layer, accelerate the absorption rate of the electrode for the electrolyte, and make the electrode fully contact with the electrolyte, so as to effectively participate in the electrochemical reaction, reduce the internal resistance of the battery during the charge and discharge cycle, and thus improve the cycle performance of the battery.
[0071] (3) The temperature during the heating and heat preservation process is lower than the decomposition temperature of the binder. The binder will not decompose (ablate) during the heating and heat preservation process, which is beneficial to maintaining the total amount of binder in the active layer and improving the cohesion and adhesion of the electrode. At the same time, the active material will not be affected by the decomposition products of the binder during the heating and heat preservation process, which is further beneficial to improving the cycle performance of the battery.
[0072] (4) During the heating and insulation process, the moisture and residual impurities adsorbed in the active layer volatilize, which helps to reduce the reaction between the moisture in the electrode and the lithium salt in the electrolyte, thereby improving the interface stability of the electrode and improving the battery cycle performance.
[0073] In some embodiments, the heating temperature and the insulation temperature are independently less than or equal to the average value of the melting point or softening point of the binder and the decomposition temperature of the binder. In this way, the binder will not decompose (ablate) during the heating and insulation process, which is beneficial to maintain the total amount of binder in the active layer, improve the cohesion and adhesion of the pole piece, and prevent the decomposition residue of the binder from affecting the active material. Moreover, at this temperature, the binder can maintain a high viscosity and the flow amplitude will not be too large, which is beneficial to maintain the stability of the pole piece structure.
[0074] In some embodiments, the heat preservation time is greater than or equal to 0.1s, and can be 0.1-2.5s, for example, it can be any point value among 0.1s, 0.2s, 0.4s, 0.6s, 0.8s, 1s, 1.2s, 1.4s, 1.6s, 1.8s, 2s, 2.2s, 2.5s, or any range value between two of them. After a certain period of heat preservation, the binder in the molten or softened state on the surface has enough time to penetrate into the active layer, thereby balancing the distribution of the binder in the active layer.
[0075] In some embodiments, the heating treatment time is 0.05 to 0.3 s, for example, any one of 0.05 s, 0.1 s, 0.15 s, 0.2 s, 0.25 s, and 0.3 s, or a range of any two of them. The heating treatment time is the time it takes for the surface of the active layer to heat up to the heating temperature. The heating rate affects the uniformity of the material. The embodiment of the present application can rapidly heat up so that the binder on the surface of the active layer can be rapidly transformed from a solid state to a molten or softened state; at the same time, it is also beneficial for heat to be rapidly transferred to the interior of the active layer, so that the binder inside the active layer also quickly melts or softens, thereby forming a whole with the binder on the surface, and promoting uniform distribution of the binder in the active layer.
[0076] In some embodiments, the insulation temperature is less than or equal to the heating temperature, and optionally, the insulation temperature is less than the heating temperature. The insulation temperature is equal to or lower than the heating temperature, which can not only maintain the melting or softening state of the binder, but also make the binder in a flowable state with a large viscosity, and at the same time, the flow range of the binder will not be too large, which is conducive to maintaining the stability of the pole piece structure without the problem of powder falling.
[0077] In some embodiments, the melting point or softening point of the binder is 140-180°C, and the decomposition temperature of the binder is 300-350°C; the heating temperature and the insulation temperature are independently 170-230°C, and optionally 190-230°C, such as any one of 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, and 230°C, or any range between two thereof. Optionally, the heating temperature can be set at 180-230°C, and the insulation temperature can be set at 180-200°C.
[0078] The heating temperature and the insulation temperature can be measured by an infrared temperature measuring instrument or other temperature tester. The heating temperature and the insulation temperature can be set within a suitable range for different binders. Within the above heating temperature and insulation temperature range, the binder can be melted or softened without decomposition, and the active substance is not interfered by the binder residue, which is conducive to maintaining the structure and performance stability of the active substance.
[0079] In some embodiments, the active material includes lithium nickel cobalt manganese oxide; optionally, in the lithium nickel cobalt manganese oxide, the molar ratio of Ni, Co, and Mn is (1-8): (1-2): (1-3), for example, it can be any point value of 8:1:1, 8:1.5:0.5, 6:2:2, 5:2:3, 5:3:2, 1:1:1 or any range value between two of them. The method of the embodiment of the present application can be used for the preparation of different lithium nickel cobalt manganese oxide positive electrode sheets, and the stability of the lithium nickel cobalt manganese oxide can be maintained during the preparation process, and the resulting battery has good cycle performance.
[0080] In some embodiments, the melting point or softening point of the binder is 140-180°C, optionally 150-180°C, such as any one of 140°C, 150°C, 160°C, 170°C, 180°C or any range between two thereof. By using a low melting point or low softening point binder, the binder can be melted or softened by heating and keeping the active layer warm at a relatively low temperature, thereby achieving redistribution of the binder, which is beneficial to reducing the temperature during the heating and keeping warm process, thereby reducing the probability of structural damage of the lithium nickel cobalt manganese oxide, and further beneficial to improving the cycle stability of the pole piece.
[0081] In some embodiments, the decomposition temperature of the binder is 300-350°C, optionally 300-320°C, such as any one of 3000°C, 310°C, 320°C, 330°C, 340°C, 350°C or any range between two thereof. The heating temperature and the insulation temperature are both lower than the decomposition temperature of the binder. Heating and insulation of the active layer below the decomposition temperature can melt or soften the binder, thereby achieving redistribution of the binder, and can also reduce the probability of structural damage of the lithium nickel cobalt manganese oxide, thereby improving the cycle stability of the electrode.
[0082] In some embodiments, the number average molecular weight of the binder can be set to (35-150)×10 4 , optionally (45~150)×10 4 , for example 35×10 4 , 40×10 4 45×10 4 , 50×10 4 , 60×10 4 70×10 4 ,80×10 4 ,90×10 4 , 100×10 4 , 120×10 4 , 140×10 4 , 150×10 4Any point value in or the range value between any two of them. The number average molecular weight is a way of characterizing molecular size, which is the total weight of all molecules in a polymer sample divided by the total number of molecules. Gel chromatography (GPC) can be used, and polystyrene (PS) can be used as a standard to test the number average molecular weight of the binder. Generally, the melting point or softening point of the binder usually has a certain relationship with its molecular weight. Within the range of the number average molecular weight, the binder has a lower melting point or softening point, which helps to implement the heating and insulation steps of the embodiments of the present application at low temperatures.
[0083] As an example, the binder may include one or more of polyvinylidene fluoride, polyvinylidene fluoride, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, and optionally polyvinylidene fluoride.
[0084] In some embodiments, the active layer further includes a conductive agent, which includes one or more of conductive carbon black, carbon nanotubes, and graphene. Such a conductive agent can transfer the heat from the surface of the active layer to the inside of the active layer through electrons, so that the positive electrode sheet is heated evenly, which is conducive to promoting the uniform distribution of the binder in the entire active layer.
[0085] The mass content of each substance in the active layer can be set as required.
[0086] For example, the mass content of the active substance in the active layer may include but is not limited to 90% to 98%, such as 95% to 98%, for example, any point value among 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or a range value between any two of them.
[0087] The mass content of the binder and the conductive agent in the active layer can independently include but are not limited to 0.5% to 5%, such as 1% to 5%, for example, any one of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range between any two of them.
[0088] In some embodiments, the heating treatment and the heat preservation treatment each independently include laser irradiation treatment.
[0089] Laser irradiation treatment uses a laser to generate a laser beam and irradiate it. Using laser as a heating source has the characteristics of high energy density in a short time and high heating efficiency, which can quickly heat the active layer to the required temperature. At the same time, laser irradiation also has the characteristics of controllable power, controllable wavelength, and high stability, which can effectively control the temperature of the active layer within the required range.
[0090] The heating treatment and the heat preservation treatment are both performed by laser irradiation. In actual operation, at least one group of lasers can be used to heat the active layer, and at least another group of lasers can be used to perform the heat preservation treatment. During the heating treatment or the heat preservation treatment, lasers can be provided on one side or both sides of the pole piece, and optionally on both sides of the pole piece, respectively, so as to heat and preserve the two surface layers of the active layer.
[0091] In some embodiments, the laser includes one or more of an infrared wavelength laser and a near-infrared wavelength laser. Optionally, the wavelength of the laser is 1000nm to 15μm, and optionally 1000 to 3000nm, such as 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, 2000nm, 2200nm, 2400nm, 2600nm, 2800nm, 3000nm, 5000nm, 1μm, 5μm, 10μm, 15μm, or any point value or a range value between any two. The laser wavelength is mainly related to the type of laser excitation medium, so different laser wavelengths can be obtained by selecting different laser excitation media. Infrared wavelength laser refers to a laser with a wavelength of 0.76 to 100μm, and near-infrared wavelength laser refers to a laser with a wavelength of 780 to 3000nm. The pole piece has strong absorption to infrared light and near-infrared light. When irradiated with laser in this wavelength range, it has high photothermal conversion efficiency and can heat the active layer to the required temperature in a short time.
[0092] In some embodiments, the laser generating the laser includes one or more of a neodymium-doped yttrium aluminum garnet crystal (Nd:YAG) laser, a ytterbium-doped yttrium aluminum garnet crystal (Yb:YAG) laser, a fiber laser, a CO2 laser, and an antimony arsenide laser. These lasers can generate infrared wavelength lasers or near-infrared wavelength lasers, for example, an Nd:YAG laser can emit a laser with a wavelength of 1064 nm, a Yb:YAG laser can emit a laser with a wavelength of 1030 nm, and a fiber laser can emit a laser with a wavelength of 1080 nm.
[0093] In some embodiments, the laser power in the heat treatment step is 2000-4500 W, optionally 2000-4000 W, such as 2000 W, 2200 W, 2400 W, 2600 W, 2800 W, 3000 W, 3200 W, 3400 W, 3600 W, 3800 W, 4000 W, 4200 W, 4500 W, or any range between two of them. The laser power can be set directly in the laser. Heat treatment under high-power laser is conducive to quickly heating the active layer.
[0094] In some embodiments, the laser power in the heat preservation step is 80-200 W, optionally 100-150 W, such as any one of 80 W, 100 W, 120 W, 140 W, 150 W, 160 W, 180 W, 200 W or any range between two thereof. Heat preservation under low-power laser can maintain the surface temperature of the active layer within the desired temperature range without overheating.
[0095] In some embodiments, the heating treatment step and the heat preservation treatment step each independently include a step of moving the pole piece relative to the laser. Optionally, the movement speed is 20 to 200 m / min, and optionally 20 to 60 m / min, for example, it can be any point value of 20 m / min, 30 m / min, 40 m / min, 50 m / min, 60 m / min, 70 m / min, 80 m / min, 90 m / min, 100 m / min, 120 m / min, 140 m / min, 160 m / min, 180 m / min, 200 m / min or any range value between two of them. In the preparation method of the embodiment of the present application, the heating treatment and the heat preservation treatment can be in a dynamic state, the pole piece moves relative to the laser, and the laser performs a short heating treatment and a short heat preservation treatment on the pole piece, which can increase the temperature of the active layer, and at the same time can reduce heat accumulation and reduce unnecessary side reactions.
[0096] In some embodiments, the laser irradiation treatment includes one or both of pulsed laser irradiation treatment and continuous laser irradiation treatment. Pulsed laser refers to a light pulse emitted by a laser using a pulsed working mode, and there is a certain interval between two adjacent light pulses. Continuous laser is a continuous and uninterrupted laser emitted by a continuous laser. Whether pulsed laser irradiation or continuous laser irradiation is used, the active layer can reach the desired temperature in a short time and be kept warm at the desired temperature.
[0097] In some embodiments, the method for preparing the pole piece further includes the step of compacting the pole piece after the heat preservation treatment. In the heating treatment step and the heat preservation treatment step, the binder in the active layer is redistributed, and the moisture and impurities absorbed in the active layer are volatilized, which may cause the thickness of the pole piece to change. Therefore, after the heat preservation treatment, compaction treatment is performed to facilitate the control of the thickness of the pole piece, for example, the thickness of the pole piece can be made consistent before and after the heating and heat preservation treatment. The compaction treatment can be performed at room temperature or at high temperature. For example, the temperature of the compaction treatment can be 25 to 130°C, such as any point value of 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 120°C, 130°C or any range value between two of them.
[0098] In addition, in the preparation method of the electrode sheet, the preparation method of the active layer containing active substances and binders can be carried out according to the following steps: mixing the active substances, binders and solvents to obtain slurry; coating the slurry on at least one surface of the current collector, drying and compacting to obtain the active layer.
[0099]
Pole piece
[0100] A second aspect of an embodiment of the present application provides a pole piece, which is obtained according to the preparation method of the first aspect mentioned above.
[0101] In the pole piece of the embodiment of the present application, the binder is evenly distributed, so that the pole piece has high bonding strength, high porosity, and low water content. It can still maintain good structural stability after a long period of charge and discharge cycles, which is beneficial to improving the cycle performance of the battery using the pole piece.
[0102] It can be understood that, in terms of structure, the pole piece may include a current collector and an active layer disposed on at least one surface of the current collector, wherein the active layer includes an active material and a binder. Meanwhile, the pole piece may be prepared by the preparation method of the first aspect.
[0103] In some embodiments, the bonding force of the pole piece is greater than or equal to 25 N / m, optionally 25 to 28 N / m, such as any point value of 25 N / m, 26 N / m, 27 N / m, 28 N / m or a range value between any two. The bonding force of the pole piece can be obtained by testing a high-speed rail tensile machine. The pole piece of the embodiment of the present application has a high bonding force, which is conducive to maintaining the stability of the pole piece during the battery cycle, thereby improving the cycle performance of the battery.
[0104] In some embodiments, the water content of the pole piece is ≤60ppm, optionally 25-60ppm, such as any point value of 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, 55ppm, 60ppm or any range value between two thereof. The water content of the pole piece refers to the mass content of water in the pole piece, which can be measured by a moisture meter. At low water content, it helps to reduce the phenomenon of water in the pole piece reacting with lithium salt in the electrolyte, thereby improving the interface stability of the pole piece and improving the battery cycle performance.
[0105]
Battery
[0106] A third aspect of an embodiment of the present application provides a battery, which includes the electrode sheet according to the second aspect.
[0107] The above-mentioned pole piece has high bonding force, high porosity, low water content, and good structural stability. The battery containing the pole piece will also show good cycle performance and long battery life.
[0108] The active material in the above-mentioned pole piece may include a positive electrode material of nickel cobalt lithium manganese oxide, so the pole piece can be used as a positive electrode of a battery.
[0109] Generally, the battery may further include a negative electrode plate, an electrolyte, a separator, an outer package, etc. Meanwhile, the battery of the embodiment of the present application may include one or more of a battery cell, a battery module, and a battery pack.
[0110] 1. Negative electrode
[0111] The negative electrode sheet may include a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector and comprising a negative electrode active material, a binder, and a conductive agent.
[0112] Among them, the negative electrode current collector may include but is not limited to a metal current collector, a carbon current collector, a conductive resin current collector, a composite current collector of metal and resin, etc., more specifically, copper, nickel, titanium, iron and their respective alloys, stainless steel, carbon fiber, carbon nanotubes (CNT), graphite, etc.
[0113] The negative electrode active material may include one or more of graphite, hard carbon, soft carbon, mesophase carbon microspheres, graphene, silicon, and silicon dioxide. The mass content of the negative electrode active material in the negative electrode active layer may include but is not limited to 90% to 98%, such as 95% to 98%, for example, any one of 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or any range between two of them.
[0114] The conductive agent in the negative electrode plate may include but is not limited to acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, graphene, etc. The mass content of the conductive agent contained in the negative electrode plate in the active layer is but is not limited to 0.5% to 10%, such as 1% to 5%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or any point value or any range value between two of them.
[0115] The negative electrode active layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). The mass content of the thickener in the active layer includes, but is not limited to, 0.5% to 5%, such as 1% to 5%, including but not limited to any one of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any range between two of them.
[0116] 2. Electrolytes
[0117] The electrolyte can be used as a carrier for ion transmission in the battery. In the battery of the embodiment of the present application, the electrolyte used can be a solid electrolyte, such as a polymer electrolyte, an inorganic solid electrolyte, etc., but is not limited thereto; the electrolyte can also be an electrolyte. The above-mentioned electrolyte includes a solvent and a lithium salt dissolved in the solvent.
[0118] Among them, the solvent can be a non-aqueous organic solvent, for example, it can include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB) and ethyl butyrate (EB), preferably two or more.
[0119] The lithium salt may include one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium bis(oxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalatophosphate) and LiTFOP (lithium tetrafluorooxalatophosphate), for example, one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium bis(oxalatoborate), LiDFOB (lithium difluorooxalatoborate), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) and LiFSI (lithium bis(fluorosulfonyl)imide).
[0120] The electrolyte may also contain other additives, such as vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), succinonitrile (SN), adiponitrile (ADN), glutaronitrile (GLN), hexanetrinitrile (HTN), 1,3-propane sultone (1,3-PS), vinyl sulfate (DTD), methylene disulfonate (MMDS), 1-propylene-1,3-sultone (PST), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), 1,4-butane sultone (1,4-BS), ethylene sulfite (DTO), dimethyl sulfite (DMS), diethyl sulfite (DES), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP) and tris(trimethylsilyl) borate (TMSB), but are not limited thereto.
[0121] 3. Isolation film
[0122] The battery also includes an isolation membrane stacked between the positive electrode plate and the negative electrode plate, which is used to separate the positive electrode plate from the negative electrode plate so that electrons in the battery cannot pass freely, preventing the two electrodes from short-circuiting due to contact, while allowing ions in the electrolyte to pass freely between the positive and negative electrodes.
[0123] The isolation membrane can be any porous structure isolation membrane with electrochemical stability and mechanical stability, such as a single-layer or multi-layer film of one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).
[0124] 4. Outer packaging
[0125] The battery may include an outer packaging, which may be used to encapsulate an electrode assembly including a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.
[0126] The outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; or a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0127] The outer packaging can be cylindrical, square or any other shape. Figure 1 As an example, the outer packaging shape of a battery cell is a square structure.
[0128] Reference Figure 2The outer package may include a shell 01 and a cover plate 02. The shell 01 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 01 has an opening connected to the receiving cavity, and the cover plate 02 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 03 through a winding process or a lamination process. One or more electrode assemblies 03 are encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 03.
[0129] 5.Battery cells, battery modules, battery packs
[0130] The battery of the embodiment of the present application may be at least one of a battery cell, a battery module, and a battery pack. According to different packaging forms, batteries are divided into battery cells, battery modules, and battery packs. Among them, a battery cell is the most basic unit of a secondary battery, including an electrode assembly and an electrolyte. The electrode assembly is usually composed of a positive electrode sheet, a negative electrode sheet, and an isolating member. The positive electrode sheets and the negative electrode sheets are alternately stacked, and an isolating film is arranged between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain a bare cell, or a bare cell after winding. The cell is placed in a casing, an electrolyte is injected, and the casing is sealed to obtain a battery cell. The battery cell mainly relies on the movement of metal ions in the electrolyte between the positive electrode sheet and the negative electrode sheet to work.
[0131] In some battery packaging technologies, one or more battery cells can be integrated into a battery module first, and then one or more battery modules can be assembled into a battery pack. In other battery packaging technologies, one or more battery cells can be directly installed in a box to form a battery pack, eliminating the intermediate state of the battery module, thereby reducing the mass of the battery pack and increasing the energy density of the battery.
[0132] refer to Figure 3 , which is an example of a battery module. In the battery module, multiple battery cells 04 can be arranged in sequence along the length direction of the battery module. Of course, they can also be arranged in any other way. Further, the multiple battery cells 04 can be fixed by fasteners.
[0133] Optionally, the battery module may further include a housing having a receiving space, and a plurality of battery cells 04 are received in the receiving space.
[0134] refer to Figure 4 and Figure 5 , which is used as an example of a battery pack. The battery pack may include a battery box and a plurality of battery modules 05 disposed in the battery box. The battery box includes an upper box body 06 and a lower box body 07, and the upper box body 06 can be covered on the lower box body 07 to form a closed space for accommodating the battery module 05. The plurality of battery modules 05 can be arranged in the battery box in any manner.
[0135]
Electrical devices
[0136] An embodiment of the present application further provides an electrical device, which includes the battery of the third aspect described above.
[0137] The battery disclosed in the embodiment of the present application can be used in an electrical device using the battery as a power source, or in various energy storage systems using the battery as an energy storage element, to provide electrical energy. The above battery exhibits the advantages of good cycle performance and long life. Therefore, after the battery is applied to various electrical devices, it is beneficial to improve the user experience of various electrical devices.
[0138] The electrical devices may include but are not limited to mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Among them, the electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and the spacecraft may include airplanes, rockets, space shuttles and spacecraft, etc. As the electrical devices, the battery cells, battery modules or battery packs in the battery may be selected according to their usage requirements.
[0139] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the battery, a battery pack or a battery module can be used.
[0140] The following detailed description of the embodiments of the present application is given. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0141] [Example]
[0142] Example 1
[0143] 1) Lithium nickel cobalt manganese oxide positive electrode sheet
[0144] The present embodiment provides a nickel cobalt lithium manganese oxide positive electrode sheet and a preparation method thereof. The nickel cobalt lithium manganese oxide positive electrode sheet comprises an aluminum foil and a positive electrode active layer disposed on two surfaces of the aluminum foil, wherein the positive electrode active layer comprises nickel cobalt lithium manganese oxide, conductive carbon black, carbon nanotubes and PVDF.
[0145] The preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet comprises the following steps:
[0146] 96wt% lithium nickel cobalt manganese oxide (molar ratio Ni:Co:Mn=8:1:1), 1.0wt% conductive carbon black, 0.5wt% carbon nanotubes, 2.5wt% PVDF (number average molecular weight 600,000, i.e. 60×10 4 ; melting point 172°C, decomposition temperature 310°C) were mixed, and then N-methylpyrrolidone was added for stirring and dispersion to prepare a positive electrode slurry containing nickel cobalt lithium manganese oxide. The positive electrode slurry was coated on aluminum foil and dried, and cold pressed to obtain a double-sided loading of 0.6g / 1540.25mm 2 , compacted density is 3.5g / cm 3 Nickel cobalt manganese oxide lithium positive electrode sheet.
[0147] The cold pressed products are subjected to heating treatment and heat preservation treatment in sequence.
[0148] Heating treatment: The nickel cobalt manganese oxide positive electrode sheet is moved at a constant speed of 20m / min under the laser. A 2000W Nd:YAG laser is set on both sides of the nickel cobalt manganese oxide positive electrode sheet. The surface temperature of the active layer contained in the nickel cobalt manganese oxide positive electrode sheet is heated to 200℃ (heating temperature) by the laser.
[0149] Insulation treatment: Then, under the irradiation of two other 100W fiber lasers arranged along the movement direction of the lithium nickel cobalt manganese oxide positive electrode sheet and arranged on both sides of the lithium nickel cobalt manganese oxide positive electrode sheet, the surface layer of the active layer contained in the lithium nickel cobalt manganese oxide positive electrode sheet was kept at 190°C (insulation temperature) for 1s (insulation time).
[0150] Then, the mixture was cooled to 25°C and rolled.
[0151] 2) Lithium-ion battery
[0152] This embodiment also provides a lithium-ion battery, which includes an electrode assembly (bare cell) composed of the above-mentioned lithium nickel cobalt manganese oxide positive electrode sheet, graphite negative electrode sheet, and isolation film, as well as an electrolyte and an outer package. The bare cell is placed in the outer package, and the electrolyte infiltrates the bare cell.
[0153] Lithium-ion batteries can be assembled as follows:
[0154] 95wt% artificial graphite, 1.0wt% conductive carbon black, 2.0wt% styrene-butadiene rubber (SBR) and 2.0wt% sodium carboxymethyl cellulose (CMC) were mixed, added with deionized water, stirred, and dispersed to form negative electrode slurry. Then the negative electrode slurry was coated on Cu foil, and after both sides were completed, it was dried, cold pressed, cut, and sliced to prepare a graphite negative electrode sheet.
[0155] The graphite negative electrode sheet, the separator, and the nickel cobalt manganese oxide positive electrode sheet are stacked in order, so that the separator is located between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare battery cell. The bare battery cell is placed in an outer package, injected with a prepared electrolyte, and packaged, injected, formed, vented, and other processes to obtain a lithium-ion battery (battery cell).
[0156] Example 2
[0157] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the electrode sheet movement speed is 60 m / min, the heating laser power is 3000 W, the heating temperature is 190° C., and the holding time is 0.33 s. Others are the same as embodiment 1.
[0158] Example 3
[0159] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the electrode sheet movement speed is 200 m / min, the heating laser power is 4000 W, the heating temperature is 180° C., and the holding time is 0.1 s. The rest is the same as embodiment 1.
[0160] Example 4
[0161] The difference between this embodiment and embodiment 3 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the heat preservation time is 0.5s. The rest is the same as embodiment 3.
[0162] Example 5
[0163] The difference between this embodiment and embodiment 3 is that in the preparation method of the lithium nickel cobalt manganese oxide positive electrode sheet, the heat preservation time is 2 seconds. The rest is the same as embodiment 3.
[0164] Example 6
[0165] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the molar ratio of nickel cobalt manganese oxide is Ni:Co:Mn=6:2:2, the heating laser power is 3500W, and the heating temperature is 210° C. The rest is the same as embodiment 1.
[0166] Example 7
[0167] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the molar ratio of nickel cobalt manganese oxide is Ni:Co:Mn=5:2:3, the heating laser power is 4000W, and the heating temperature is 220° C. The rest is the same as embodiment 1.
[0168] Example 8
[0169] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the molar ratio of Ni:Co:Mn in the nickel cobalt manganese oxide lithium is 1:1:1, the heating laser power is 4500W, and the heating temperature is 230° C. The rest is the same as embodiment 1.
[0170] Example 9
[0171] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the molecular weight of PVDF is 1 million and the melting point of PVDF is 175° C. The rest is the same as embodiment 1.
[0172] Example 10
[0173] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the molecular weight of PVDF is 1.5 million and the melting point of PVDF is 180° C. The rest is the same as embodiment 1.
[0174] Embodiment 11
[0175] The difference between this embodiment and embodiment 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the molecular weight of PVDF is 450,000 and the melting point of PVDF is 150° C. The rest is the same as embodiment 1.
[0176] Example 12
[0177] The difference between this embodiment and embodiment 1 is that in the method for preparing the lithium nickel cobalt manganese oxide positive electrode sheet, the laser in the laser heating step is a Yb:YAG laser, and the laser in the laser heat preservation step is a CO2 laser. The rest is the same as embodiment 1.
[0178] Embodiment 13
[0179] The difference between this embodiment and embodiment 1 is that in the method for preparing the lithium nickel cobalt manganese oxide positive electrode sheet, the laser in the laser heating step is a fiber laser, and the laser in the laser heat preservation step is an antimony arsenide laser. The rest is the same as embodiment 1.
[0180] [Comparative Example]
[0181] Comparative Example 1
[0182] The difference between this comparative example and Example 1 is that in the preparation method of the nickel-cobalt-manganese-lithium oxide positive electrode sheet, no heating treatment and heat preservation treatment are performed. The rest is the same as Example 1.
[0183] Comparative Example 2
[0184] The difference between this comparative example and Example 1 is that in the preparation method of the nickel-cobalt-manganese-lithium oxide positive electrode sheet, no heat preservation treatment is performed. The rest is the same as Example 1.
[0185] Comparative Example 3
[0186] The difference between this comparative example and Example 1 is that in the preparation method of the nickel cobalt manganese oxide lithium positive electrode sheet, the heating temperature is 320° C. and the heating laser power is 5500 W. The rest is the same as Example 1.
[0187] Comparative Example 4
[0188] The difference between this comparative example and Example 6 is that in the preparation method of the nickel-cobalt-manganese-lithium oxide positive electrode sheet, no heating treatment and heat preservation treatment are performed. The rest is the same as Example 6.
[0189] Comparative Example 5
[0190] The difference between this comparative example and Example 7 is that in the preparation method of the nickel-cobalt-manganese-lithium oxide positive electrode sheet, no heating treatment and heat preservation treatment are performed. The rest is the same as Example 7.
[0191] Comparative Example 6
[0192] The difference between this comparative example and Example 8 is that in the preparation method of the nickel-cobalt-manganese-lithium oxide positive electrode sheet, no heating treatment and heat preservation treatment are performed. The rest is the same as Example 8.
[0193]
Electrochemical performance and structural testing
[0194] The positive electrode sheets and lithium-ion batteries of the embodiments and comparative examples were tested to obtain relevant test results.
[0195] 1. Heating temperature, insulation temperature and insulation time
[0196] Table 1. Test results of battery electrochemical performance of Examples 1 to 5 and Comparative Examples 1 to 3 (PVDF melting point 172°C, decomposition temperature 310°C; Ni:Co:Mn=8:1:1)
[0197]
[0198] Table 2. Performance test results of positive electrode sheets of Examples 1 to 5 and Comparative Examples 1 to 3
[0199]
[0200] The test results in Table 1 show that when the positive electrode sheet is not subjected to heating treatment and heat preservation treatment (Comparative Example 1), after the positive electrode sheet is applied to the battery, the capacity retention rate of the battery after 500 cycles at 1C is 96.63%; on this basis, adding a heating treatment step, but without heat preservation treatment (Comparative Example 2), the cycle performance of the battery is improved less, and the capacity retention rate of 500 cycles at 1C is 96.97%. Combined with the test results in Table 2, this may be that only heating treatment is not enough to improve the electrode sheet, the bonding force in the positive electrode sheet does not change much, and the improvement in the cycle is not great.
[0201] In contrast, in Examples 1 to 5, by sequentially performing heating treatment and heat preservation treatment during the preparation of the positive electrode sheet, the capacity retention rate of the corresponding battery after 500 cycles at 1C can be increased to 97.2% or more. Figure 7 As shown in the figure, the cycle performance has been improved. This is mainly because after the heating treatment and the heat preservation treatment, the binder is fully balanced, so that the bonding force of the positive electrode sheet is increased, and the water evaporates during the heat preservation process, and the porosity of the positive electrode sheet is improved (the increase in the liquid absorption rate reflects that the porosity of the positive electrode sheet has increased, which can improve the wettability of the positive electrode sheet); and during the heating treatment and the heat preservation process, the heating temperature and the heat preservation temperature are both lower than the decomposition temperature of the binder, and the nickel cobalt manganese oxide can remain stable and is not affected by the impurities generated by the decomposition of the binder during the heating process, such as Figure 8 XRD diagram of the positive electrode sheet of Example 1 before and after heating and heat preservation treatment, and Fig. 9 The SEM images of the positive electrode sheet of Example 1 before and after the heating treatment and the heat preservation treatment reflect that the crystal form, structure and crystallinity of the lithium nickel cobalt manganese oxide do not change significantly after the heating treatment and the heat preservation treatment. Under the combined effect of these phenomena, the interface performance of the positive electrode sheet is greatly improved, and the impedance of the positive electrode sheet is reduced, thereby improving the battery cycle performance.
[0202] During the heating treatment and heat preservation treatment, the heating temperature and the heat preservation temperature can be set in a temperature range greater than or equal to the melting point of the binder and less than the decomposition temperature of the binder, and more specifically can be set in the first 50% of the temperature range between the melting point of the binder and the decomposition temperature of the binder (that is, set to be greater than or equal to the melting point of the binder, and less than or equal to the average value of the melting point of the binder and the decomposition temperature of the binder), and the heating temperature and the heat preservation temperature can be the same or different (the heat preservation temperature can be higher than the heating temperature or lower than the heating temperature), and the battery cycle performance can be improved as shown in Examples 1 to 3. Among them, when the heat preservation temperature is lower than the heating temperature, the battery exhibits better cycle performance. When either the heating temperature or the heat preservation temperature is too high, for example, in Comparative Example 3, setting the heating temperature at 320°C will reduce the battery cycle performance. According to the test results in Table 2, this is mainly due to the excessively high temperature causing the binder to decompose, which reduces the bonding strength of the positive electrode sheet; and the decomposition products of the binder react with the active material lithium nickel cobalt manganese oxide, and the decomposition residues remain in the electrode sheet without being removed, which increases the side reactions between the positive electrode sheet and the electrolyte, causing the interface performance of the positive electrode sheet to deteriorate.
[0203] At the same time, the cycle performance of the battery is related to the holding time. As shown in Examples 3 to 5, within the holding time range of 0.1 to 2 seconds, the 500-cycle capacity retention rate of the battery at 1C first increases and then decreases as the holding time increases. Therefore, a suitable holding time can be selected to achieve better cycle performance of the battery.
[0204] In addition, the test results also show that compared with comparative examples 1 to 3, the positive electrode sheets of embodiments 1 to 5 have higher gram capacity and better rate performance (higher 3C capacity retention rate), which shows that heating treatment and heat preservation treatment can not only improve the battery cycle performance, but also improve the gram capacity and rate performance.
[0205] 2.Ni:Co:Mn molar ratio
[0206] Table 3. Battery electrochemical performance test results at different Ni:Co:Mn molar ratios (PVDF melting point 172°C, decomposition temperature 310°C)
[0207]
[0208] Table 4. Performance test results of positive electrode sheets at different Ni:Co:Mn molar ratios
[0209]
[0210] According to the test results in Table 3, the method of sequentially performing heating treatment and heat preservation treatment during the preparation process is suitable for preparing positive electrode sheets with different Ni:Co:Mn molar ratios, and can improve the cycle performance of the battery. For example, the capacity retention rate of Example 6 after 500 cycles at 1C is higher than that of Comparative Example 4 using the same Ni:Co:Mn molar ratio but not subjected to heating treatment and heat preservation treatment; the capacity retention rate of Example 7 after 500 cycles at 1C is higher than that of Comparative Example 5 using the same Ni:Co:Mn molar ratio but not subjected to heating treatment and heat preservation treatment; the capacity retention rate of Example 8 after 500 cycles at 1C is higher than that of Comparative Example 6 using the same Ni:Co:Mn molar ratio but not subjected to heating treatment and heat preservation treatment. Similarly, this is mainly because after the heating treatment and heat preservation treatment, the binder is fully balanced, so that the bonding force of the positive electrode sheet increases, and the water evaporates during the heat preservation process, the porosity of the positive electrode sheet is improved, and the interface performance of the positive electrode sheet is greatly improved, while the impedance of the positive electrode sheet is reduced, and finally the cycle performance of the battery is improved.
[0211] Similar to Examples 1 to 5, for positive electrode sheets with different Ni:Co:Mn molar ratios, after heating treatment and heat preservation treatment, in addition to excellent battery cycle performance, they also exhibit high positive electrode sheet specific capacity and rate performance.
[0212] 3. Binder molecular weight and melting point
[0213] Table 5. Battery electrochemical performance test results under different binders (PVDF decomposition temperature 310°C; Ni:Co:Mn=8:1:1)
[0214]
[0215] The test results in Table 5 show that when using PVDF with different molecular weights and melting points, the batteries have good cycle performance and rate performance after the positive electrode sheets have been heated and kept warm.
[0216] 4. Laser
[0217] Table 6. Test results of battery electrochemical performance under different lasers (PVDF melting point 172°C, decomposition temperature 310°C; Ni:Co:Mn=8:1:1)
[0218]
[0219]
[0220] According to Table 6, using a laser that can emit infrared wavelength laser or near-infrared wavelength laser to heat and insulate the positive electrode can improve the cycle performance and rate performance of the battery.
[0221]
Performance test method
[0222] (1) Adhesion strength of positive electrode
[0223] Cut the positive electrode sheet into 20*100mm 2 The test specimens of different sizes are kept for later use; the double-sided tape is used to adhere the side of the specimen to be tested, and compacted with a roller to make the double-sided tape fit the specimen completely; the other side of the double-sided tape of the specimen is adhered to the stainless steel surface, and one end of the specimen is bent in the opposite direction with a bending angle of 180°; the high-speed rail tensile testing machine is used for testing, one end of the stainless steel is fixed to the lower fixture of the tensile testing machine, the bent end of the specimen is fixed to the upper fixture, the angle of the specimen is adjusted to ensure that the upper and lower ends are in a vertical position, and then the specimen is stretched at a speed of 50 mm / min until the specimen is completely peeled off from the substrate, and the displacement and force in the process are recorded. It is generally believed that the force when the force is balanced is the bonding force of the positive electrode.
[0224] (2) Liquid absorption rate of positive electrode
[0225] Fix the positive electrode on a clean glass plate and draw electrolyte (1 mol·L - 1After that, LiPF6, EC:DMC:EMC mass ratio = 1:1:1), it is vertically contacted with the positive electrode to allow the electrode to absorb the electrolyte, and the time for the electrolyte to be absorbed is measured, and the electrolyte absorption rate is obtained by conversion.
[0226] (3) Positive electrode sheet gram capacity and 1C capacity retention rate
[0227] After cleaning one side of the positive electrode with N-methylpyrrolidone or deionized water, punch and cut it into a single-sided circular electrode with a diameter of 14 mm and weigh it; at the same time, weigh the corresponding current collector substrate under the 14 mm diameter circular piece to obtain the total loading. Calculate the active material loading according to the electrode formula.
[0228] The 2032 button cell is equipped with a negative electrode shell, nickel foam, 16 mm diameter lithium sheet, 18 mm diameter Celgard2325 separator, 0.1 g 1 mol·L -1 LiPF6 EC:DMC:EMC (mass ratio 1:1:1) electrolyte, 14mm diameter single-sided circular pole piece (active material side facing the separator) and 2032 button battery supporting positive electrode shell are assembled into 2032 button battery. The assembled button battery is tested after standing for 12 hours: at 25℃, it is charged to the upper limit of the positive electrode active material voltage at a current of 0.1C, and then charged at a constant voltage at the upper limit voltage until the current is less than 0.05C, and then stopped charging. After standing for 5 minutes, it is discharged to the lower limit of the positive electrode active material voltage at a current of 0.1C, and the discharge capacity (i.e., the initial discharge capacity C0) is recorded. The initial discharge capacity divided by the positive electrode active material loading is the positive electrode sheet gram capacity.
[0229] The button cell was charged at 25°C with a current of 1C to the upper limit of the voltage of the positive electrode active material, then charged at a constant voltage at the upper limit voltage until the current was less than 0.05C, and then stopped charging. After standing for 5 minutes, it was discharged with a current of 1C to the lower limit of the voltage of the positive electrode active material, and the discharge capacity was recorded as C1. This test method was repeated 500 times, and the discharge capacity at this time was recorded as C 500 According to C 500 The capacity retention rate at 1C @500cls = (C1-C 500 ) / C1*100%.
[0230] (4) Moisture content of positive electrode
[0231] Cut the cathode sheet to be tested into pieces with a length and width of less than 5mm, take 0.6-1g of the cut cathode sheet pieces and place them in a dry cillin bottle. Add the Karl Fischer anolyte and the Karl Fischer cathode solution into the titration cup at a volume ratio of 20:1, and connect the generating electrode, indicator electrode and air guide tube in the titration cup to the Karl Fischer moisture tester. Set the test temperature to 170℃, the actual weight of the electrode, the air flow rate to 40mL / min, the start drift to 10μg / min, the stop drift to 20μg / min, and the stabilization time to 20s to obtain the moisture content of the cathode sheet.
[0232] (5) Discharge rate (3C capacity retention rate)
[0233] The battery cell was kept at rest for 30 min at 25°C; discharged at a constant current of 0.33C to 2.8V, and then discharged at a constant current of 0.33C to 2.8V; left at rest for 1 hour at 25°C; charged at a constant current of 0.33C to a cut-off voltage (the charging cut-off voltage of Examples 6 to 8 and Comparative Examples 4 to 6 was 4.35V, and the charging cut-off voltage of other Examples and Comparative Examples was 4.25V); then charged at a constant voltage at the cut-off voltage, and the cut-off current was 0.05C.
[0234] Repeat the above steps. Record the discharge capacity C at 0.33C. 0.33 .
[0235] Let stand for 30 minutes at 25℃; discharge at 3C to 2.8V, let stand for 1 hour at 25℃, and record the discharge capacity C3 at 3C. 0.33 and C3 to obtain 3C capacity retention rate = (C 0.33 -C3) / C 0.33 *100%.
[0236] (6) DC resistance (25℃DCR@50%SOC)
[0237] The battery cell was left to stand at 25°C for 30 min, charged at a constant current of 0.33C to a cut-off voltage (the charging cut-off voltage of Examples 6 to 8 and Comparative Examples 4 to 6 was 4.35V, and the charging cut-off voltage of other Examples and Comparative Examples was 4.25V), and charged at a constant voltage at the cut-off voltage with a cut-off current of 0.05C. At this time, the state of charge (SOC) of the battery was 100%.
[0238] After standing for 5 minutes at 25°C, discharge at 0.33C, cut-off current 0.5C, adjust SOC to 50%. After standing for 1 hour at 25°C, record voltage V1.
[0239] Discharge at 5C for 30s, record the voltage V2 and the current I of 5C constant current discharge.
[0240] Stand at 25℃ for 40s, charge at 3.75C constant current for 30s. Stand at 25℃ for 1h, charge at 0.33C constant current to the cut-off voltage (the charging cut-off voltage of Examples 6 to 8 and Comparative Examples 4 to 6 is 4.35V, and the charging cut-off voltage of other Examples and Comparative Examples is 4.25V), charge at constant voltage at the cut-off voltage, and the cut-off current is 0.05C. Stand at 25℃ for 5min, and record the voltage V1'.
[0241] Then discharge at 0.33C, cut-off current 0.9C, adjust SOC to 50%, stand at 25℃ for 1h, discharge at 5C for 30s, record voltage V2', and current I' of 5C constant current discharge.
[0242] Let stand for 40 seconds at 25°C, charge at 3.75C constant current for 30 seconds, let stand for 5 minutes at 25°C. The above steps can be repeated multiple times.
[0243] The DC resistance of the battery cell at 25°C, 50% SOC, and 5C constant current discharge for 30s, that is, 25°C DCR@50% SOC = (V2-V1) / I = (V2'-V1') / I'.
[0244] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a pole piece, characterized in that: include: An active layer comprising an active material and a binder is prepared on at least one side of the current collector; Performing a heating treatment on the active layer to raise the surface temperature of the active layer to a heating temperature; Performing heat preservation treatment on the active layer so that the surface of the active layer is at a heat preservation temperature; The heating temperature and the insulation temperature are independently greater than or equal to the melting point or softening point of the binder, and less than the decomposition temperature of the binder.
2. The method for preparing a pole piece according to claim 1, characterized in that: The heating temperature and the insulation temperature are independently less than or equal to an average value of a melting point or a softening point of the binder and a decomposition temperature of the binder.
3. The method for preparing a pole piece according to claim 1 or 2, characterized in that: The heat preservation treatment time is greater than or equal to 0.1 s, and can be optionally 0.1 to 2.5 s.
4. The method for preparing a pole piece according to any one of claims 1 to 3, characterized in that: The insulation temperature is less than or equal to the heating temperature.
5. The method for preparing a pole piece according to any one of claims 1 to 4, characterized in that: The melting point or softening point of the binder is 140-180°C, and the decomposition temperature of the binder is 300-350°C; the heating temperature and the insulation temperature are independently 170-230°C, and optionally 190-230°C.
6. The method for preparing a pole piece according to claims 1 to 5, characterized in that: The active material includes lithium nickel cobalt manganese oxide; optionally, in the lithium nickel cobalt manganese oxide, the molar ratio of Ni, Co and Mn is (1-8): (1-2): (1-3).
7. The method for preparing a pole piece according to claims 1 to 6, characterized in that: The number average molecular weight of the binder is (35-150)×10 4 , optionally (45~150)×10 4 .
8. The method for preparing a pole piece according to any one of claims 1 to 7, characterized in that: The heating treatment and the heat-retaining treatment each independently include laser irradiation treatment.
9. The method for preparing a pole piece according to claim 8, characterized in that: The laser includes one or more of an infrared wavelength laser and a near-infrared wavelength laser. Optionally, the wavelength of the laser is 1000nm to 15μm.
10. The method for preparing a pole piece according to claim 8 or 9, characterized in that: The laser power in the heating treatment step is 2000-4500W, optionally 2000-4000W.
11. The method for preparing a pole piece according to any one of claims 8 to 10, characterized in that: The laser power in the heat preservation step is 80-200W, and optionally 100-150W.
12. The method for preparing a pole piece according to any one of claims 1 to 11, characterized in that: The method for preparing the pole piece further comprises the step of compacting the pole piece after the heat preservation treatment.
13. A pole piece, characterized in that: The pole piece is obtained according to the preparation method according to any one of claims 1 to 12.
14. A battery, characterized in that: The battery comprises the electrode sheet according to claim 13.
15. An electrical device, characterized in that: The electrical device comprises the battery according to claim 14.
Citation Information
Patent Citations
Battery pole piece as well as preparation method and application thereof
CN114464792A
High-energy-density high-temperature lithium ion battery and preparation method thereof
CN116207355A
Manufacture of electrode
JP1999120996A
Method for producing electrode for lithium secondary batteries
WO2016152833A1